1972
DOI: 10.1111/j.1365-2141.1972.tb05693.x
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation and Clinical Use of a New Concentrate Containing Factor IX, Prothrombin and Factor X and of a Separate Concentrate Containing Factor VII

Abstract: A method of preparation for therapeutic use of a concentrate of factors IX, 11 and X and a separate concentrate of factor VII is described. The method is based upon adsorption of the factors on DEAE-cellulose from plasma or from the supernatant after removal of factor WI. Conditions of elution are selected so that, in a single step, the factors are obtained at a suitable salt concentration and potency to permit injection of a therapeutic dose by syringe. The yield of factor IX in vitro is about 5~7 5 % and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1973
1973
2010
2010

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…On electrophoresis in polyacrylamide gel, the concentrate was found to contain all the zones present in the preparation of Dike et al [8] with some deferences in the relative intensities of the minor bands; our concentrate contained less pre-albumin, albumin and ctj-globulin than did that of Dike et al [8].…”
Section: Description Of the Dried Productmentioning
confidence: 89%
See 4 more Smart Citations
“…On electrophoresis in polyacrylamide gel, the concentrate was found to contain all the zones present in the preparation of Dike et al [8] with some deferences in the relative intensities of the minor bands; our concentrate contained less pre-albumin, albumin and ctj-globulin than did that of Dike et al [8].…”
Section: Description Of the Dried Productmentioning
confidence: 89%
“…The relevance of immunoglobulin type to hetero agglutinin activity and pyrogenicity is being pursued in the light of these results. It has been found that IgM, and rather less IgG, is eluted coincidently with the factor IX-containing fractions, using either our standard procedure or the conditions of Dike et al [8]. The 'second eluate' from the control experiment discussed above contained less IgM than the 'first eluate'.…”
Section: Pyrogenicity In Rabbitsmentioning
confidence: 95%
See 3 more Smart Citations